Analysis of Administrative Services through Online Submission of the Surabaya KNG (Klampid New Generation) Application - Tita Dwi Agustin; Yusuf Hariyoko (PT FORMOSA CENDEKIA GLOBAL, 2022)
Public services are services provided by the government to the community starting from population administration services, health services, and educational services in accordance with the 1945 Constitution regulations regarding matters to meet the basic needs of every citizen. Public services are listed in Article 1 Paragraph (1) of Law Number 25 of 2009 concerning Public Services which are activities or series in the framework of fulfilling service needs in accordance with statutory regulations for every citizen and population of goods and services that must be fulfilled by administrative state. For this reason, the government continues to develop new innovations, especially population administration so that people can easily take care of all administrative management, especially their population. Klampid New Generation) issued by the Surabaya City Population and Civil Registration Service can be an easier independent online service innovation by utilizing currently developing technology